2005
DOI: 10.1073/pnas.0409462102
|View full text |Cite
|
Sign up to set email alerts
|

Robustness, scalability, and integration of a wound-response gene expression signature in predicting breast cancer survival

Abstract: Based on the hypothesis that features of the molecular program of normal wound healing might play an important role in cancer metastasis, we previously identified consistent features in the transcriptional response of normal fibroblasts to serum, and used this ''wound-response signature'' to reveal links between wound healing and cancer progression in a variety of common epithelial tumors. Here, in a consecutive series of 295 early breast cancer patients, we show that both overall survival and distant metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
737
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 853 publications
(766 citation statements)
references
References 24 publications
21
737
1
5
Order By: Relevance
“…Some previously identified markers do have prognostic value in nodepositive breast cancer, however, since they do not identify a substantial group of patients with an excellent disease outcome, the clinical relevance as prognostic marker for this node-positive patients' group seems to be limited [13,17,18]. The only other signature that could identify a low risk group with a sufficiently good outcome within node-positive patients was the wound signature [9]. Since this wound signature is not available as a diagnostic test, its value for clinical practice seems to be limited at this moment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previously identified markers do have prognostic value in nodepositive breast cancer, however, since they do not identify a substantial group of patients with an excellent disease outcome, the clinical relevance as prognostic marker for this node-positive patients' group seems to be limited [13,17,18]. The only other signature that could identify a low risk group with a sufficiently good outcome within node-positive patients was the wound signature [9]. Since this wound signature is not available as a diagnostic test, its value for clinical practice seems to be limited at this moment.…”
Section: Discussionmentioning
confidence: 99%
“…To allow more extensive analyses, follow-up data of all patients with 1-3 positive nodes from the previously described series by Van de Vijver [8], were updated, blinded to the 70-gene prognosis-signature [9].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the molecular features that define this wound-like phenotype are evident at an early cancer and predict increased likelihood of metastasis and death in breast, lung, and gastric cancer. 29 In a subsequent study of 295 early breast carcinomas, Chang et al 30 showed that both overall survival and distant metastasis-free survival are significantly diminished in patients whose carcinomas expressed this 'wound-response signature' compared to tumors that did not express this signature. 30 At this point, it is not clear whether the observed genetic changes in our current study are related to breast cancer initiation or are acquired 'reactive' genetic alterations which are more associated with tumor progression.…”
Section: Macro-environment Of Breast Carcinoma F Moinfar Et Almentioning
confidence: 99%
“…Cancer cells do not invent new pathways, but resurrect the pre-existing but dormant signaling pathways that were active during embryonic development or normal physiological condition. In recent studies (Chang et al, 2004(Chang et al, , 2005, gene expression signatures from experimental condition mimicking wound healing process were used to measure how much tumors may be like wounds, and developed a model to predict cancer progression based on wound healing gene expression signature. Patients carrying the wound healing signature had a significantly increased risk of metastasis when compared with patients who lack the signature, indicating that genomic data from normal physiological condition can help to predict the prognosis of cancer patients.…”
Section: Integrative Functional Genomicsmentioning
confidence: 99%